Validitas Hukum Percakapan WhatsApp Sebagai Alat Bukti Elektronik dalam Kasus Kekerasan Seksual Berbasis Digital di Indonesia. - Lirih Tyas Anjarwati; Aditya Wiguna Sanjaya (Universitas Medan Area, 2026)
This article aims to analyze the legal validity of WhatsApp conversations as electronic evidence in cases of digital sexual violence, as well as the limits of digital privacy protection in law enforcement. The discussion focuses on the use of conversations in private communication spaces as a basis for legal liability, using the case of a student in the Specialist Medical Education Program at the University of Indonesia as an illustration, as this case has sparked debate regarding the balance between the right to privacy and the interest in protecting victims. To approach this issue, this study draws on Ronald Dworkin’s “law as integrity” theory and John Rawls’s theory of justice, which emphasize the importance of moral consistency in law enforcement and the protection of those in vulnerable positions. Data were collected through a literature review using legislative, conceptual, case-based, and socio-legal approaches, and then analyzed qualitatively. This study concludes that WhatsApp conversations can serve as electronic evidence provided they meet the requirements of authentication, relevance, the pro-principle, and the principle of proportionality. The novelty of this study lies in the understanding that the right to digital privacy is not absolute but rather a relational and contextual right, and thus may be limited to protect victims and achieve justice.